1982
DOI: 10.1177/002224378201900404
|View full text |Cite
|
Sign up to set email alerts
|

Sample Size Effects on Chi Square and Other Statistics Used in Evaluating Causal Models

Abstract: A simulation study of the effects of sample size on the overall fit statistic provided by the LISREL program indicates the statistic is well behaved over a wide range of sample sizes for simple models. However, this statistic is apparently not chi square distributed for more complex models when samples are relatively small, and will reject the hypothesized model too often. A set of additional measures suggested by various researchers for evaluating causal models also is examined. These statistics are well beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
174
1
8

Year Published

1992
1992
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(195 citation statements)
references
References 19 publications
12
174
1
8
Order By: Relevance
“…The chi-squared statistic was significant (p < .01) in each CFA, but this was not unexpected since it is known to be sensitive to large sample sizes (Bearden, Sharma, & Teel, 1982;Marsh, Balla, & McDonald, 1988). The construct reliability estimates for the Pphubbing scale (.93), the involvement scale (.96), the attitude scale (.92), the cell phone addiction (.81), and the cell phone conflict scale (.94) were acceptable.…”
Section: Resultsmentioning
confidence: 82%
“…The chi-squared statistic was significant (p < .01) in each CFA, but this was not unexpected since it is known to be sensitive to large sample sizes (Bearden, Sharma, & Teel, 1982;Marsh, Balla, & McDonald, 1988). The construct reliability estimates for the Pphubbing scale (.93), the involvement scale (.96), the attitude scale (.92), the cell phone addiction (.81), and the cell phone conflict scale (.94) were acceptable.…”
Section: Resultsmentioning
confidence: 82%
“…Specifically, the 2 /df value of 3.202 falls within a range of acceptable values from 2 to 5 as suggested by Marsh and Hocevar (1988). Other practical fit indices demonstrated that the measurement model fits the data well (RMSEA = 0.079, CFI = 0.917, and NFI = 0.884) (Bearden et al, 1982;Hair et al, 1998;Marsh and Hocevar, 1988). Subsequently, reliability and construct validity were examined.…”
Section: Measurement Validationmentioning
confidence: 80%
“…Both start from the same set of theoretical and measurement equations but differ in how they approach the parameter estimation problem. Assume a structural equation model with a set of latent exogenous variables (ξ i ) measured by indicators x i and associated measurement error δ i , and a set of latent endogenous variables (η j ) measured by indicators y j and Note: Does not include simulation studies that are focused on the relative performance of different fit indices (e.g., Bearden, Sharma, & Teel, 1982;Curran, West, & Finch, 1996;Hu & Bentler, 1998) or on the analysis of specific issues, such as the estimation of interaction effects (e.g., Chin et al, 2003), between-group differences (e.g., Qureshi & Compeau, 2009), measurement model misspecification (e.g., Jarvis, MacKenzie, & Podsakoff, 2003) and item parceling (e.g., Bandalos, 2002;Kim & Hagtvet, 2003;Nasser & Wisenbaker, 2003). associated measurement error ε j .…”
Section: Cbsemmentioning
confidence: 99%